Main liver manifestations in sickle cell disease (Research, Society and Development, 2022)
Sickle cell disease (SC) is an autosomal recessive genetic disease that occurs due to a mutation in the β-globin gene. Among the main genotypes are hemoglobin SS (HbSS), a homozygous form responsible for a series of complications, which vary according to the affected system. Within the digestive tract, the hepatobiliary system is the most affected. Sickle cell liver diseases, so called hepatic manifestations in sickle cell disease, can be classified into acute and chronic, which can generate serious consequences for carriers. This literature review, conducted between July and October 2022, has as its main objective to elucidate the main liver manifestations in sickle cell disease, as well as to discuss possible behaviors to reduce mortality in this group. For the composition of this review, articles published between the years 2017 and 2022 were selected, from the search for keywords through the following electronic databases: PUBMED Central (PMC) and Scielo. In total, 21 articles were selected. It can be concluded from the analysis of these that the pathophysiology and clinical manifestations of sickle cell liver diseases are well clarified in the literature. However, the ways to prevent these complications and treatment still need more studies.